The Importance of the Study of the Microelement Composition Diet of Children in the Prophylaxis of Microelementosis - Djuraeva, Zilola A. (International Journal of Psychosocial Rehabilitation, 2020)
The concentration of micronutrients in food products of animal origin (the national dish – Khalis, chakka, milk, honey, egg yolk, kidney, liver) in the region of Zarafshan valley: egg yolk, the national dish halise, kidneys, liver and honey - rich in iron halise, meat and egg yolk- rich in zinc, egg white - rich in copper egg yolk, dairy products - rich in calcium, meat and egg white - rich in sodium and potassium meat, honey – magnesium.Consider the most optimal and safe for the prevention and correction of deficiency microelementoses, the diet to use foods rich in micronutrients.